Pengaruh Scaffolding Konseptual dalam Pembelajaran Group Investigation Terhadap Prestasi Belajar Fisika Siswa SMA dengan Pengetahuan Awal Berbeda - Rindu Rahmatiah; Supriyono Koes H.; Sentot Kusairi (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2016)
The aim of this research is to find out the effect of conceptual scaffolding strategy in Group Investigation towards physics achievement of senior high school students with different prior knowledge levels. This research was quasi-experimental research with factorial design. The population of this research was all grade XI students of SMAN 2 Mataram. The sample of this research was choosen by a cluster random sampling technique, each class consisted of 39 and 38 students. The experimental group learned lessons by conceptual scaffolding strategy in Group Investigation while the control group learned lessons by Group Investigation. The students of each groups were divided into two category based on their prior knowledge, these were students with higher prior knowledge and students with lower prior knowledge. Two way analysis of varian (two way anova) was used as the data analysis technique. The result of this research are: 1) there is physics achievement difference between the students who learn lessons by conceptual scaffolding strategy in Group Investigation and the students who learn lessons by Group Investigation; 2) there is physics achievement difference between the students with different prior knowledge levels; and 3) there is no effect of interaction between the strategy and the studentÃ¢â¬â¢s prior knowledge toward physics achievement.